Scenario of Health Camps in Nepal - Pandey, A; Paudel, P; Paudel, L (Journal of Nepal Health Research Council, 2011)
It has become a rising trend in Nepal to conduct health camps. This article tries to give an overview about the direction to which this aspect of community based service is going to and also points out a few pros and cons related to this. A couple of issues has also been raised like; ethical issues, lack of governing bodies and a lack of national policy, unavailability of data upon health camps and so forth. Above all, this article tries to clarify the importance ofconducting health camps in a country like ours and if properly conducted this has a balanced benifit to all.Keywords: health camp, community based service